APPLICATION OF INFORMATION TECHNOLOGY FOR MONITORING OF BRIDGES CONSTRUCTIONS - Hulytska, L. V.; Korol, E. A.; Shymanska, O. S. (Science and Transport Progress, 2010)
The article is dealt with а variant of usage of database technologies in the transport communication sphere, particularly for introduction of integrated methodology of evaluation of technical-and-operational condition of bridge structures on highways of general use.